Ecotourism Perception and Engagement Classification Among Residents of a Nature City in the Philippines - Mark Gabriel Wagan Aguilar; Rainiel Bryan Villanueva Domasian (Journal of Tourismology)
It is very important to study the behavior of people who have gone to and continue to visit nature-based attractions to learn about their appreciation to nature and the actions they take to help out in protecting them, given that tourism has been linked to environmental degradation as a sector that is prone to overconsumption, resulting in significant waste and pollution. Guided by a descriptive research design and employing a quantitative research approach, the researchers determined the perception and level of engagement of 383 people on ecotourism activities adapted from the Shallow-Deep Model of Ecotourism by Acott et al (1998) used in the Classification Framework on Ecotourism by Alampay and Libosada (2005), resulting in determining whether they are passive or active eco-tourists engaging in shallow or deep ecotourism. Findings serve as an indicator of the position of Filipinos as advocates for ecotourism since the respondents, of all people, are expected to have a strong positive perspective and deep engagement on ecotourism, being from a place that is known for its natural resources, as well as being used as a guide for ecotourism managers and educators in coming up with an effective environmental education program.